Aerospace series. Screws, pan head, offset cruciform recess, coarse tolerance normal shank, medium length thread, in alloy steel, cadmium plated. Classification: 1 100 MPa (at ambient temperature) / 235 °C. (30th April 2016) - British Standards Institution,
No abstract available